Intérêt général, intérêt individuel et raison collective : perspectives à partir de l’œuvre de Proudhon - Édouard Jourdain (Astérion)
What Proudhon’s work calls collective reason questions the notion of the general interest in order to distinguish itself from Rousseau’s terminology. The former allows the articulation between individuals and groups through both an anthropological and a deliberative procedure approaches. This conception of socialization will produce the unity that could result from the check and balance in normative terms. Thus, collective reason englobes the totality of social interactions. In the political sphere, the concept allows the understanding of general or collective interest not as the monist unity embodied by the sovereignty of the state, but by a pluralistic unity marked by the autonomy of the collective beings subordinating the state to their service.